(3NRf GSJQLGY GdeYdheGJ (B/s - (3GdfOGa, YUGe GMeOs; (3GdTfWj, Gjef s; (3TbQ, YGeQ YHO Gddg s ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3CSGSjGJ GSJQLGY GdeYdheGJ , GdJMdjd GdehVhYj , GddZI aj GdGSJQLGY , GdHMK aj eQGUO GdHjGfGJ , GdYhGed GdeDKQI Ydi GdCOGA aj GSJQLGY GdeYdheGJ , GdWQb GdBdjI dGSJQLGY GdeYdheGJ (B.s
(3eQGLY U(B.254s
Keywords: (3GdeYdheGJs; (3JcfhdhLjG GdeYdheGJs; (3NOeGJ GdeYdheGJs; (3Yde GdeYdheGJs